2014
DOI: 10.1111/sms.12359
|View full text |Cite
|
Sign up to set email alerts
|

The Coaching Behavior Scale for Sport (CBSS): A psychometric evaluation of the Swedish version

Abstract: The present study validated a Swedish version of the 47-item Coaching Behavior Scale for Sport (CBS-S). Sample 1 consisted of 506 team sport athletes [262 men and 244 women; mean age: 22.20, standard deviation (SD) = 3.90] distributed across 41 coaches at the two highest national levels of various sports. Athletes completed the CBS-S and established questionnaires of coaching behaviors (LSS), self-confidence (CSAI-2R), and coach-athlete relationship (CART-Q). An additional sample of 39 basketball players (21 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…From this point of view in this study, it was found that 65% of the participants coming from a total of 13 countries were male, while 35% were female and their average age was 25,16±4,53. In a similar study conducted by Carlsson and Lundqvist (2016) in Sweden, 52% of the participants were male, while 48% were female and the average age of the group was 22,20. In a study conducted by Baker et al (2003) with participants from 14 different branches, 51% of the participants were male and 49% were female and the average age was 17, 8. In another study conducted by Baker et al (1999) with 205 participants from 7 different branches, 47% of the participants were male and 53% were female.…”
Section: Discussionmentioning
confidence: 83%
“…From this point of view in this study, it was found that 65% of the participants coming from a total of 13 countries were male, while 35% were female and their average age was 25,16±4,53. In a similar study conducted by Carlsson and Lundqvist (2016) in Sweden, 52% of the participants were male, while 48% were female and the average age of the group was 22,20. In a study conducted by Baker et al (2003) with participants from 14 different branches, 51% of the participants were male and 49% were female and the average age was 17, 8. In another study conducted by Baker et al (1999) with 205 participants from 7 different branches, 47% of the participants were male and 53% were female.…”
Section: Discussionmentioning
confidence: 83%
“…Coaches consider that verbal or physical abuse is necessary to improve the ability of young athletes (Yabe et al 2018). However, coaches tend to be unaware of the negative impacts of their behaviors on young athletes (Carlsson and Lundqvist 2016). Further, it has been reported that coaches using abuse also have a history of experiencing abuse from their coaches in their younger age (Yabe et al 2018), which mean that young athletes who has experienced abuse can be abusive coaches in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of young athletes' sporting experiences differ according to age (Chan et al 2012), and their coaches play a pivotal role in creating nurturing environment (Ommundsen et al 2006). Various behaviors of coaches affect young athletes both positively or negatively (Carlsson and Lundqvist 2016). Coaches' positive behaviors towards athletes can elicit enjoyment and motivation, and induce aspiration towards challenging and mastery experiences (Mollerlokken et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Coaches desire to achieve wins and their behavior ranges from positive to negative (Swigonski et al 2014). They are presumably unaware of their negative behavior and overestimate the positive nature of their behavior in relation to athletes (Carlsson and Lundqvist 2016). Although they do not intend to harm athletes, coaches' abusive behavior results in detrimental, long-term effects on young athletes (Stirling and Kerr 2008).…”
Section: Discussionmentioning
confidence: 99%